Potensi Beras Organik dalam Mewujudkan Ekonomi Berkelanjutan Berbasis Etika Islam dan Kemitraan Syariah - Sofianiyatin, Lilik; Khusniatul Muna, Dina (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
The increasing demand for organic rice is driven by public awareness of health and environmental sustainability, making this sector have high economic value. This study uses a qualitative method with a case study approach, involving observation and interviews with KNOC managers and partners. The results of the study indicate that the concept of organic rice not only provides better economic benefits than conventional farming, but is also in line with the principles of Islamic economics, such as justice, blessings, and public welfare. The application of Islamic economic principles in organic rice businesses is realized through a fair partnership system, transparency, farmer empowerment, and sharia-compliant profit sharing. Thus, the development of organic rice in Ngawi has the potential to improve community welfare in a sustainable manner and become an environmentally friendly sharia-based economic model. Keywords: organic rice, Islamic economics, blessings, sustainability, partnership, KNOC, community welfare.